Kinetic of Nitrate Reduction by Nanoscale Zero-Valent Iron on the Basis of Different Models Estimation - Tang, Jianshe; Xiang, Li; Zhao, Feng (Asian Journal of Chemistry, 2013)
In this study, a more fine-grained spherical nanoscale zero valent iron (nZVI) with diameter of 20-50 nm was synthesized in ethanol-water mixed solvent. The structures and physical properties of nZVI were characterized by transmission electron microscope, X-ray diffractometer analyzer. Reactivity of the nZVI was affirmed by denitrification of nitrate. The removal efficiency of nitrate in the presence of nZVI was 80 % within 1 h at optimal conditions. In view of this, the nZVI is efficient to removing nitrate and offers a great potential to the removal of other contaminants in water. The kinetic estimations in terms of three kinds model (the first-order, the second-order and the Langmuir-Hinshelwood) under the conditions of different initial nitrate concentration or different nZVI dosage were compared with each other. The result was obtained that the S-model fits the denitrification very well.